Prevalence, Clinical Features, and In-hospital Outcome of Fatty Liver Disease in Acute Aortic Dissection: A Single-Center Retrospective Study - Zuo, Yifan; Cai, Xin; Wang, Zhiwei; Hu, Zhipeng; Wu, Zhiyong; Zhang, Min; Yu, Anfeng; Liu, Liang; Xing, Yun (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background and Aims: Fatty liver disease (FLD) has emerged as a major public issue in China. We aim to investigate prevalence, clinical features, and in-hospital outcome of FLD in acute aortic dissection (AAD) patients. Methods: Data of 379 AAD patients from 2017 to 2019 at Renmin hospital of Wuhan University was retrospectively collected and divided according to age and FLD absence. Propensity score matching was used for minimal confounding. We compared their physical environmental parameter of onset, clinical features, and in-hospital outcome. Results: The mean age was 52.0±11.5 years in type A and 55.1±11.4 in type B. 25.0% of type A and 19.2% of type B AAD patients had FLD. Logistic regression indicated a negative association between FLD and age, both in type A [unadjusted odds ratio (OR) 0.958 (per 1 year), 95% confidence interval (CI) 0.930-0.988, p = 0.0064] and type B [unadjusted OR 0.943 (per 1 year), 95% CI 0.910-0.978, p = 0.0013]. After matching, type A with FLD had onset with a lower air quality index (AQI) of 68.5 [interquartile range (IQR) 46.0-90.0] and a lower Pm 2.5 concentration of 36.0 μg/m3 ( IQR 23.0-56.0) compared with non-FLD group. In Kaplan-Meire estimation, FLD was associated with higher risk of in-hospital mortality in type B AAD (p=0.0297). Conclusion: The prevalence of FLD in AAD decrease with age, both in type A and type B AAD. Type A AAD patients with FLD had onset with better air quality parameters compared with non-FLD group. FLD was associated with higher risk of in-hospital mortality in type B AAD.